FRI0607 Long-term and optimization of infliximab in refractory uveitis associated to behÇet disease. multicentre study of 100 patients. (15th June 2017) - Casas, LC Domínguez; Calvo-Río, V; Beltrán, E; S-Bursόn, J; Mesquida, M; Adán, A; Hernandez, M; L-Longo, F; H-Grafella, M; Valls, E; M-Costa, L; Sellas, A; et al.
Abstract : Objectives: To assess the long term efficacy and optimization of Infliximab (IFX) in refractory Uveitis of Behçet Disease (BD) Methods: Multicentre study of Uveitis associated-BD refractory to conventional immunosupressive drug. Ocular inflammation was evaluated with "SUN criteria" (Am J Ophthalmol 2005;140:509–516) and the macular thickening with OCT. Results are expressed as mean±SD or median [IQR] (comparison, Wilcoxon test) Results: We studied 100 patients/180 affected eyes (54M/46W), mean age 40.7±10.1. The ocular pattern was panuveitis (n=62), posterior (27) and anterior uveítis (11). Before IFX they received iv MP (28), cyclosporine (75), azathioprine (56), metotrexate (43) and others (33). IFX dose ranged between 3–5mg/kg/4 or 8 weeks. In patients in remission IFX was optimized (n=28) or stopped (n=20). Conclusions: IFX is an effective long term-treatment in refractory Uveitis of BD. Optimization and even discontinuation of IFX after remission is possible. Disclosure of Interest: None declared